Transabdominal ultrasound as accurate and sensitive modality for diagnosis of ovarian dermoid cyst: a tertiary care hospital experience (Journal of Fatima Jinnah Medical University, 2019)
Background: Transabdominal ultrasound is readily available, cost effective and first line investigation for pelvicpathologies in girls of adolescent age group. It avoids unnecessary radiation exposure due to CT imaging. Ovariandermoid cyst is common benign pathology among young girls. In present study we have determined thetransabdominal ultrasound sensitivity, specificity and diagnostic accuracy for diagnosis of dermoid cyst of ovary takinghistopathology as gold standard.Patients and methods: This cross-sectional study was conducted at Diagnostic Radiology Department, Sir Ganga RamHospital Lahore from 25th Nov 2014 to 24th May 2015. In this study 150 patients (age 6 to 25 years) were includedwith clinical suspicion of ovarian mass or lower abdominal pain. Transabdominal sonography was carried out anddiagnosis i.e. presence of ovarian dermoid cyst or its absence were recorded. All the patients (with a lowerabdominal/pelvic mass) underwent surgery either by laparoscopy or laparotomy (therapeutic/diagnostic) andpostoperative specimen were sent for histopathology. The results of transabdominal sonogram and histopathologywere compared taking histopathology as gold standard.Results: After comparison of results of transabdominal sonography with histopathology the sensitivity, specificity oftransabdominal ultrasound were 92.7%, 87.5% and diagnostic accuracy was 91.3%. Negative and positive predictivevalues were 95.3% and 81.3% respectively.Conclusion: The transabdominal ultrasound is very accurate and sensitive modality for diagnosis of ovarian dermoidcyst. Moreover transabdominal ultrasound is easily available first line imaging technique for the diagnosis of thiscommon pelvic lesion (dermoid cyst) among adolescent and young girls.
Keywords: Transabdominal Ultrasound, Ovarian Dermoid Cyst, Mature Ovarian Teratoma